Collecting Data on Charismatic Mini-Fauna: Public Participation and the Dragonfly Mercury Project - Pritz, Colleen; Nelson, Sarah (Maine Policy Review, 2017)
The Dragonfly Mercury Project (DMP) engages citizen scientists in collection of dragonfly larvae for mercury analysis in national parks, allowing for national-scale assessment of this neurotoxic pollutant. DMP goals for citizen scientist engagement are to (1) provide opportunity for biodiversity discovery; (2) connect people to parks; and (3) provide a vehicle for mercury education and outreach. Over 90 parks and 3,000 citizen scientists have participated in the project. Here we summarize information about citizen groups who participated in 2014–2016. High school students (20%), interns and youth groups (24%), and local community groups (15%) comprised the majority of participants. Park liaisons reported that the project achieved internal and external communication that otherwise would not have occurred. Opportunities for improvement included further curriculum and workforce development. Ultimately, citizen scientists gained new perspectives and practiced civic skills while project scientists and resource managers gained data and insights on mercury in foodwebs.
Keywords: dragonflies; citizen science; National Park Service; mercury bioaccumulation